The Effectiveness of Education Programs on the Management of Acute Coronary Syndrome Patients: A Scoping Review - Yulis Setiya Dewi; Achmad Fauzi; Albertina Dete Tabik; Aqmarina Abidah; Johanes Eban B. Dorman; Yulmira Maria Tisel; Ninuk Dian Kurniawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Acute Coronary Syndrome (ACS) is a serious condition that requires quick treatment to prevent complications and death. The education program is one of the effective interventions in improving the understanding, compliance, and quality of life of ACS patients. Objective: This study aims to evaluate the effectiveness of educational programs in ACS patient management through a scoping review. Method: This study uses the scoping review method with the PRISMA-Scr protocol. Data was obtained from Scopus, ProQuest, PubMed, and EBSCO databases with relevant keywords and publication of articles in the last 5 years (2019–2024). Articles that met the inclusion criteria were analyzed using a descriptive approach. Quality assessment is carried out using the Joanna Briggs Institute (JBI) Critical Appraisal tool. Results: Of the initial 34,668 articles, 12 articles with good and medium quality were selected. Effective educational programs include behavioral, media, distance, and group-based methods. These interventions have been shown to improve patient understanding, medication adherence, and quality of life as well as reduce anxiety and depression. The instruments used included PPE-15, HADS-A, HADS-D, SF-12, HeartQoL and GENEActiv accelerometer questionnaires. Conclusions: Educational programs based on a patient-centered care approach (PCC), technology, and physical exercise have proven to be effective in improving ACS patient management. Behavioural and media-based education, such as traffic light labels for nutrition understanding, is able to support lifestyle changes and patient rehabilitation. Intensive education also has a positive impact in reducing the risk of long-term complications.